2001
DOI: 10.1111/j.1460-9568.2001.01360.x
|View full text |Cite
|
Sign up to set email alerts
|

Visual interhemispheric transfer to areas 17 and 18 in cats with convergent strabismus

Abstract: Commissural connections between primary visual cortical maps of the two hemispheres are essential to unify the split representation of the visual field. In normal adult cats, callosal connections are essentially restricted to the border between areas A17 and A18, where the central vertical meridian is projected. In contrast, early convergent strabismus leads to an expanded callosal-receiving zone, as repeatedly indicated by anatomical experiments. We investigated here the functional correlates of this widespre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 65 publications
(95 reference statements)
1
19
0
Order By: Relevance
“…Therefore, callosal neurons within an ocular dominance column also display their own orientation selectivity and the recent findings do not contradict electrophysiological evidence of matched orientation between thalamic and callosal inputs both in normal and strabismic cats (15).…”
Section: Relation Of Callosal Patches To Other Columnar Modulesmentioning
confidence: 87%
See 2 more Smart Citations
“…Therefore, callosal neurons within an ocular dominance column also display their own orientation selectivity and the recent findings do not contradict electrophysiological evidence of matched orientation between thalamic and callosal inputs both in normal and strabismic cats (15).…”
Section: Relation Of Callosal Patches To Other Columnar Modulesmentioning
confidence: 87%
“…In 1997, Schmidt et al (14) used a combination of deoxyglucose, optical recording and retrograde tracing in strabismic cats and concluded that callosal projections were preferentially established between columns of the same orientation, as is the case for intrahemispheric long-range projections. However, although converging thalamic and callosal inputs still appear to be matched for orientation in strabismic cats (15), it is known that the overall distribution of callosal projections and terminals is profoundly modified (16). Therefore, the relation of the pattern of callosal connections to the columnar systems of the visual cortex in normal adults cannot be inferred from data obtained in animals with altered visual experience.…”
Section: Relation Of Callosal Patches To Other Columnar Modulesmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports indicate that damage to the posterior corpus callosum produces inability to judge depth in patients with damage of the optic chiasm, and section of the corpus callosum may reduce the proportions of binocular cells (27)(28)(29). In addition, experimentally induced early strabismus leads to an expanded callosal receiving zone in areas 17 and 18; in these conditions callosal cells also show decreased binocularity, decreased ability to respond to fastmoving stimuli, a small receptive field size, and poor orientation selectivity (19). Midline visual deficits (30) and impairment of interhemispheric depth comparisons when using head movements to determine relative depth (31) have been reported in acallosal humans.…”
Section: Visual Callosal Fibers: Midline Fusion and Depth Perceptionmentioning
confidence: 99%
“…It is possible that the corpus callosum is involved in more subtle mechanisms of depth perception than stereopsis (which is specifically defined as binocular disparity), such as relative motion or parallax, that is, using the differences in relative motion of near and far objects to judge depth (31). In this context, it has been suggested that visual callosal fibers participate in predicting trajectories of moving objects across the midline, and in the generation of binding mechanisms in the central visual field (19,20).…”
Section: Visual Callosal Fibers: Midline Fusion and Depth Perceptionmentioning
confidence: 99%